Case Study : Baker’s Cottage / Natasha Ezreen Mohamed Nasir - Mohamed Nasir, Natasha Ezreen (2021)
In this Case Study, I would like to summarize that Baker’s Cottage is a bakery and cafe that serve a bunch of high-quality pastries using traditional recipes, which has been highlighted on their tagline “Traditional Goodness You Can Taste”. Even though the company has been opened in the early 90’s, they managed to maintain their business until now and officially altered their selves as a quick-service-restaurant (QSR) business. Moreover, 123 retail outlets have been running with new concept design that is more cozy. The purpose of this case study is to identify the entrepreneur’s background and entrepreneur’s competencies. By doing this case study, we can acknowledge that Baker’s Cottage has developed in many aspects in order to improve their business and service when we refer to their entrepreneur’s competencies.